1992
DOI: 10.1007/bf00625951
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thyroid, testes, kidney and autonomic nervous system function in lead-exposed workers

Abstract: The objective of the study was to assess whether moderate occupational exposure to lead may be associated with early changes in potential target organs (thyroid, testes, kidney, autonomic nervous system). Workers exposed to lead in a lead acid battery factory (n = 98; mean blood lead 51 micrograms/dl, range 40-75 micrograms/dl) and 85 control workers were examined. None of the indicators of kidney function (in urine: retinol-binding protein, beta 2-microglobulin, albumin, N-acetyl-beta-D-glucosaminidase; in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 45 publications
5
35
1
1
Order By: Relevance
“…In a study of 98 workers from a lead acid battery factory with a mean PbB of 51 μg/dL, the mean hemoglobin concentration was not significantly different than in an unexposed group of 85 subjects (mean PbB, 21 μg/dL). However, four exposed workers, but no controls, had hemoglobin levels below the level considered as the limit value for defining anemia (13 µg/dL) (Gennart et al 1992a). Similar lack of correlation between PbB and hemoglobin was reported in a study of 94 Israeli lead workers with a mean PbB of 38.1 μg/dL (range, 6-113 μg/dL) .…”
Section: Health Effectssupporting
confidence: 72%
See 1 more Smart Citation
“…In a study of 98 workers from a lead acid battery factory with a mean PbB of 51 μg/dL, the mean hemoglobin concentration was not significantly different than in an unexposed group of 85 subjects (mean PbB, 21 μg/dL). However, four exposed workers, but no controls, had hemoglobin levels below the level considered as the limit value for defining anemia (13 µg/dL) (Gennart et al 1992a). Similar lack of correlation between PbB and hemoglobin was reported in a study of 94 Israeli lead workers with a mean PbB of 38.1 μg/dL (range, 6-113 μg/dL) .…”
Section: Health Effectssupporting
confidence: 72%
“…Some of these studies indicated that correlations can be seen at PbB of <40 μg/dL (Lauwerys et al 1974;Selander and Cramer 1970;Solliway et al 1996), although the slope may be different (less steep) than at PbBs >40 μg/dL. In a study of 98 occupationally exposed subjects (mean PbB, 51 μg/dL) and 85 matched referents (mean PbB, 20.9 μg/dL), it was found that log ZPP and log ALA in urine correlated well with PbB (Gennart et al 1992a). In the exposed group, the mean ZPP was 4 times higher than in the comparison group, whereas urinary ALA was increased 2-fold.…”
Section: Health Effectsmentioning
confidence: 99%
“…In men occupationally exposed to lead, blood lead levels equal to or higher than 400 µg L -1 have been associated with reduced sperm count, poor semen motility, and abnormal sperm morphology, particularly of the sperm head (69)(70)(71)(72)(73)(74)(75)(76)(77)(78). Effects on the reproductive endocrine function have been less consistent (71,74,(79)(80)(81)(82)(83).…”
Section: Effects Of Occupational Exposure To Metals On Reproductive Pmentioning
confidence: 99%
“…Effects on the reproductive endocrine function have been less consistent (71,74,(79)(80)(81)(82)(83). Reduced sperm count and concentration, and lower motility were found in lead workers with blood lead levels lower than 400 µg L -1 (78,(84)(85).…”
Section: Effects Of Occupational Exposure To Metals On Reproductive Pmentioning
confidence: 99%
“…With respect to the autonomic nervous effect of lead, three studies observed significant differences between exposed and unexposed groups 27,54,55) , and one report found no association between exposure and R-R interval variations 56) . The autonomic nervous function in 36 lead workers aged 21-35 yr and 15 textile workers aged 22-29 yr was assessed by the CV RR with the two components (CCV HF and CCV LF ) 27) .…”
Section: Figmentioning
confidence: 99%